Novel NGT-DEMATEL Method for Interrelationship Management of Safety Conformity in a Bottling Process Plant - Shedrach Aliakwe Martins; Sunday Ayoola Oke; Adeyemi Adebayo Ogundare; Joseph Ifeolu Orisaleye; Samuel Bolaji Aderibigbe; John Rajan; Swaminathan Jose; Abdulfatai Folawuyo Ahmed (Universitas Atma Jaya Yogyakarta, 2026)
The NGT (nominal group technique) is a structured brainstorming decision-making method with the ability to reach a quick consensus and incorporate all voices in safety management. The DEMATEL method is used to establish safety measure influential parameters, their interdependence, and their impacts on each other. This article presents the NGT-DEMATEL method based on the NGT and DEMATEL methods and uses real-time bottling process data to test the proposed method. The results reveal that for segments 1 to 5, the casual groups, having positive (Sr – Sc) values, are sorters (0.3523), rescuers (0.6271), sugar handles (0.4332), haulage drivers (1.0958), and haulage truck mates (0.2442) for segment 1; sighters (0.2981), washer operators (0.7459), and technical operators (utilities) (0.3761) for segment 2; sugar lifters (2.8805) and ETP technicians (1.1935) for segment 3; forklift technician (1.6203) for segment 4; kitchen (0.0399) for segment 5. However, the effect groups are forklift drivers (-0.8338), chip neck removers (-1.5044) and extra bottle removers (-0.4143) for segment 1; filler operators (-0.3078), palletizers/depalletizers (-0.0421), chip neck removers (-0.9615), packers/unpackers (-0.1086) for segment 2; syrup mixers (-2.5812), laboratory technicians (-1.4505) and water technicians (-0.0423) for segment 3; welders (-1.1380) and battery changers/technicians (-0.4823) for segment 4; security (-2.4973), and contractor 2 (safety boot suppliers) (-1.0840) for segment 5. The most important criteria in segments 1 to 5 are forklift drivers, sighters, syrup mixers, welders, and security. The principal novelty of this article is that it introduces a procedure to concurrently incorporate consensus and the voices of workers while establishing the interrelationships of the various workers using the NGT-DEMATEL method. This is the first article to develop and use NGT-DEMATEL for safety conformity in the bottling process plant.